Exenatide and Dapagliflozin Combination Enhances Sertoli Cell Secretion of Key Metabolites for Spermatogenesis - Ribeiro, João C. (2022)
The incidence of metabolic diseases such as type 2 diabetes mellitus (DM) and obesity has been increasing dramatically. Both diseases are closely linked and new approaches for type 2 DM treatment aim to enable weight loss. A combined therapy of dapagliflozin and exenatide has been used against type 2 DM, influencing allbody glucose dynamics. Spermatogenesis is highly dependent on the metabolic cooperation established between Sertoli cells (SCs) and developing germ cells. To study the effects of dapagliflozin and exenatide on SC metabolism, mouse SCs were treated in the presence of sub-pharmacologic, pharmacologic, and supra-pharmacologic concentrations of dapagliflozin (50, 500, 5000 nM, respectively) and/or exenatide (2.5, 25, 250 pM, respectively). Cytotoxicity of these compounds was evaluated and the glycolytic profile, glycogen content assay, and lipid accumulation of SCs were determined. Dapagliflozin treatment decreased fat cellular deposits, demonstrating its anti-obesity properties at the cellular level. Polytherapy of exenatide plus dapagliflozin increased lactate production by SCs, which has been reported to improve sperm production and quality. Thus, the results herein suggest that the use of these two pharmacological agents can protect male fertility, while improving their glucose homeostasis and inducing weight loss.